Analyzing Advanced Approaches to Appraisal of Tax Impact on Efficiency of Business Entities in Conditions of Uncertainty - E. A. Danchikov; S. N. Kovalenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article analyzes the impact of taxation on finance result, one of key indicators of estimating the efficiency of business entity work. The author studies the effect of direct and indirect taxes on efficiency of organization work in the context of conventional-variable and conventional-constant costs and the influence of choosing organizational-legal form on the taxation system of business entity. Advantages and drawbacks of the taxation system are shown and the problem of changing the taxation system in certain industries is investigated. The need to optimize taxation as a tool of cutting costs and increasing economic benefits of the entity and its efficiency is substantiated. Key methods of taxation optimization capable of organization efficiency growth by reducing the tax burden are demonstrated. The article shows the impact of taxes on such finance indicators as solvency, liquidity, profitability, business activity and finance stability, which in their turn affect business efficiency. Positive (stimulating) and adverse influence of taxes on business entity functioning in conditions of uncertainty is studied.